2018
DOI: 10.1055/s-0038-1676567
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Difference between Cemented and Uncemented Femoral Stem Extensions in Revision Knee Arthroplasty?

Abstract: A stem is usually recommended for the femoral component in revision total knee arthroplasty (TKA) for reasons of alignment, fixation, and bone loss. However, the optimal method of fixation for the femoral component stem remains controversial. We queried the prospective revision TKA database of one surgeon and performed a clinical and radiographic evaluation of 84 knee revisions in which a femoral component stem extension was implanted. There was no established protocol for fixation of the femoral stem during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…On the contrary, studies by Gomez et al, Gililland et al and Jacquet et al studied all aseptic causes of primary TKA failure [ 19 21 ]. The rest of the studies included all indications of revision TKAs including loosening, infection, instability, osteolysis or polywear, stiffness, malposition, arthrofibrosis and patellar subluxation [ 16 , 22 25 ]. Majority of the studies included in this systematic review were from the United States of America (USA).…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, studies by Gomez et al, Gililland et al and Jacquet et al studied all aseptic causes of primary TKA failure [ 19 21 ]. The rest of the studies included all indications of revision TKAs including loosening, infection, instability, osteolysis or polywear, stiffness, malposition, arthrofibrosis and patellar subluxation [ 16 , 22 25 ]. Majority of the studies included in this systematic review were from the United States of America (USA).…”
Section: Resultsmentioning
confidence: 99%
“…Although some favour one method over the other, [13][14][15] most conclude that both methods give good fixation in these patients. [16][17][18][19] To our knowledge, this is the first long-term RCT comparing micromotion of cemented and hybrid fixation in patients undergoing rTKAs. Strict inclusion and exclusion criteria which were used at the start of this study allowed an objective comparison of these two methods of fixation.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, clinical studies indicate that pediculated systems may be suitable for use with the augments as described above [20]. In their study with 84 knee revisions, Lachiewizc et al found no significant difference between cemented and uncemented pediculated fixation when used in knee revisions due to loosening [21]. Similarly, a recent meta-analysis failed to demonstrate that any fixation technique was superior [22].…”
Section: Stem Fixation/stemsmentioning
confidence: 99%